An LC-MS/MS method for quantitation of methylparaben, benzophenone, and pharmaceutical compounds from domestic wastewater - Barreiro, Juliana Cristina [UNESP]; Florentino, Anna Patricya; Furlani, Izadora Liranco; Silva, Gustavo H. R. [UNESP]; Cass, Quezia Bezerra (Frontiers Media Sa, 2022)
An analytical method was developed to quantify a mixture of acetaminophen, metoprolol, methylparaben, carbamazepine, naproxen, estrone, estradiol, diclofenac, benzophenone, ibuprofen, progesterone, and mefenamic acid from domestic wastewater samples. To match fast and efficient chromatographic separation for different classes of compounds, an automated scouting liquid chromatographic system was associated with the experimental design produced by the DryLab (R) software. HLB cartridges were used to extract the analytes from the sample matrix, which was followed by detection and quantitation by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The lowest detection limits were found for acetaminophen and carbamazepine (0.625 pg L-1) and metoprolol (0.4 pg L-1).
Keywords: pharmaceutical compounds; liquid chromatography; wastewater; chromatographic modeling and simulation; DryLab (R)